Ecofeminism in Indonesia: women’s empowerment and environmental activism on social media - Ananda, Dewi; Briandana, Rizki (Jurnal Studi Komunikasi, 2025)
In the digital age, social media platforms like Instagram have become significant tools for grassroots activism, particularly in addressing environmental and gender issues. In Indonesia, where climate change intersects with low levels of literacy, efforts to empower mothers with climate knowledge are increasingly vital. Mothers are often at the forefront of managing domestic and environmental challenges, yet their access to climate literacy remains limited. This study aims to analyse the literacy discourse and climate crisis issues raised by @bbbbookclub in the #ClimateLiteracyforMothers campaign on Instagram. Using a qualitative approach and applying Marie-Anne Paveau’s discourse analysis, the research is grounded in the theoretical frameworks of cyberculture and digital activism. The findings reveal four dominant discourses: the urgency of positioning mothers as agents of social change; critical reflections on environmental policy and patriarchal-capitalist systems; the use of religious and local cultural narratives to communicate environmental values; and lifestyle transformation as a form of climate action. These discourses illustrate how digital activism can shape new forms of environmental engagement among marginalised communities. The study also identifies elements of ecofeminist ideology that underpin the campaign, highlighting how women’s empowerment and environmental advocacy can converge in online spaces.